FeOOH nanodot / coralline carbon nitride bifunctional catalyst, preparation method and application
By loading FeOOH nanodots on coral-like carbon nitride and constructing a FeOOH/CCN bifunctional catalyst, the problems of photogenerated carrier separation and recombination of g-C3N4 photocatalyst were solved, the degradation efficiency of pollutants was improved, and an efficient photo-Fenton reaction was achieved.
Patent Information
- Application Number
- CN202510831090.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-09-19
AI Technical Summary
Existing g-C3N4 photocatalysts have problems such as difficult separation and easy recombination of photogenerated carriers, low specific surface area and poor visible light capture ability, resulting in low pollutant degradation efficiency.
By loading iron oxyhydroxide (FeOOH) nanodots on coral-like carbon nitride (CCN), a bifunctional catalyst was constructed, and the FeOOH/CCN composite catalyst was synthesized by hydrothermal and calcination methods to achieve the synergistic progress of photocatalysis and Fenton reaction, spontaneously producing the H2O2 required for the Fenton reaction.
The specific surface area of the photocatalyst and the photogenerated charge transfer efficiency are improved, the degradation rate of pollutants is enhanced, and efficient photo-Fenton system degradation performance is achieved.
Smart Images

Figure CN120662357A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite material preparation, and particularly relates to an iron oxyhydroxide (FeOOH) nanodot / coral-like carbon nitride (CCN) dual-function catalyst, a preparation method and an application thereof. Background Art
[0002] Water pollution is a global issue facing humanity, and research on pollutant degradation is advancing, particularly for tetracycline (TC) and oxytetracycline (OTC). Photocatalytic and Fenton-ion technologies are highly effective degradation technologies. As a focal point of semiconductor catalysts in recent years, g-C3N4 has garnered widespread attention from scholars both domestically and internationally. However, bulk g-C3N4 suffers from drawbacks such as difficulty separating and easily recombinating photogenerated charge carriers, poor visible light capture, and a low specific surface area. Therefore, to improve its photocatalytic efficiency, g-C3N4 was first morphologically modified to significantly increase its specific surface area. Simultaneously, FeOOH was used as a Fenton center, enabling simultaneous photocatalytic and Fenton reactions in the reaction system. The presence of FeOOH also facilitates photogenerated charge transport and reduces recombination of photogenerated carriers. A novel photocatalyst preparation method is needed to modify the g-C3N4 morphology, increase its specific surface area, facilitate photogenerated charge transport, reduce recombination of photogenerated carriers, and improve its pollutant degradation rate. Summary of the Invention
[0003] The purpose of the present invention is to provide a FeOOH nanodot / coral-like carbon nitride bifunctional catalyst, a preparation method and an application thereof. The FeOOH / CCN bifunctional catalyst effectively promotes the separation and transfer of photogenerated carriers, thereby improving the photocatalytic degradation efficiency.
[0004] The technical solution of the present invention:
[0005] A dual-function iron oxyhydroxide nanodot / coral-like carbon nitride catalyst presents a coral-like structure with side branches extending from the main body. The branch diameter is about 100 nm, the main body length can reach 1-2 μm, and the catalyst is densely arranged.
[0006] A method for preparing a dual-functional iron oxyhydroxide nanodot / coral-like carbon nitride catalyst comprises synthesizing CCN by hydrothermal and calcination methods, and then preparing a FeOOH quantum dot / CCN composite catalyst by a template-free and additive-free in-situ coprecipitation technique.
[0007] Beneficial effects of the present invention:
[0008] The precursors and products of the catalyst preparation method of the present application are all green chemistry and will not pollute the environment. The present invention designs a dual-reaction center catalytic system with a synergistic effect by loading FeOOH nanodots on CCN. The photocatalytic reaction center is mainly CCN, and the Fenton reaction center is mainly FeOOH. The photocatalytic reaction and the Fenton reaction are carried out simultaneously. By changing the carbon nitride morphology to increase the specific surface area of the catalyst, the special coral morphology is conducive to the transfer of photogenerated charge carriers and also provides a large number of reaction active sites for the photo-Fenton system. At the same time, the H2O2 required for the Fenton reaction with FeOOH as the reaction center can be spontaneously generated by the system. The large number of active sites, strong visible light response and rapid carrier transport reflect the strong degradation performance of the self-Fenton system. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0010] Figure 1 a is the XRD patterns of BCN, CCN, and 5% FeOOH / CCN.
[0011] Figure 1 b is a graph showing the nitrogen adsorption desorption of BCN, CCN, and 5% FeOOH / CCN.
[0012] Figure 2 FT-IR spectra of CCN and 5% FeOOH / CCN.
[0013] Figure 3 a and b are SEM images of CCN.
[0014] Figure 4 a and b are SEM images of 5% FeOOH / CCN.
[0015] Figure 5 a and b are TEM images of 5% FeOOH / CCN.
[0016] Figure 6 a is the TC curve of catalyst photodegradation.
[0017] Figure 6 b is the pseudo-first-order kinetic model of TC photodegradation by catalyst.
[0018] Figure 6 c is the UV-visible absorption spectrum of TC degraded by 5%-FeOOH / CCN under different irradiation times.
[0019] Figure 7 a is the degradation curve of TC under different catalyst dosages in 5%-FeOOH / CCN system.
[0020] Figure 7 b is the pseudo-first-order kinetic model of TC degradation in 5%-FeOOH / CCN system with different catalyst dosages.
[0021] Figure 7 c is the degradation curve of OTC under different catalyst dosages in 5%-FeOOH / CCN system.
[0022] Figure 7 d is the pseudo-first-order kinetic model of OTC degradation in 5%-FeOOH / CCN system with different catalyst dosages.
[0023] Figure 8 UV-visible diffuse reflectance spectra of CCN and 5% FeOOH / CCN.
[0024] Figure 9 PL images of CCN and 5% FeOOH / CCN.
[0025] Figure 10 These are the photocurrent diagrams of CCN and 5% FeOOH / CCN.
[0026] Figure 11 This is the hydrogen peroxide production curve of the catalyst. DETAILED DESCRIPTION
[0027] In order to solve the problems in the background technology, a novel preparation method and application of iron oxyhydroxide (FeOOH) nanodots / coral-like carbon nitride (CCN) bifunctional catalyst is invented. CCN is synthesized using a simple hydrothermal and calcination method. Iron oxyhydroxide (FeOOH) nanodots / coral-like carbon nitride (CCN) bifunctional catalyst is constructed using a template-free and additive-free in-situ synthesis technology. The photocatalytic reaction center is mainly CCN, and the Fenton reaction center is mainly FeOOH. The photocatalytic reaction and Fenton reaction proceed simultaneously. The H2O2 required for the Fenton reaction can be spontaneously generated by the system. First, the prepared CCN is added to an anhydrous ethanol solution and stirred evenly. Then, the FeCl3·6H2O solution is added dropwise to the above solution. Then, a certain amount of NH4HCO3 is added. Finally, the sample is dried to obtain the product. The pollutant degradation efficiency of the catalyst of the present application is effectively improved.
[0028] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0029] Example 1
[0030] (1) Preparation of CCN
[0031] First, 1.6g of urea and 1g of melamine were added to a beaker containing 16mL of deionized water and stirred for 3 hours to prepare a precursor solution. The solution was then transferred to a 20mL reactor and placed in an oven at 180°C for 20 hours, reaching a fill level of 80%. After the container cooled naturally, the solution was repeatedly washed with ethanol and then water using a centrifuge. Finally, the product was dried at 60°C for 24 hours. The dried product was then heated to 550°C in a muffle furnace at a rate of 1.5°C / min and reacted for 4 hours to obtain the product.
[0032] (2) Preparation of FeOOH / CCN
[0033] First, 0.05g of CCN and 0.0082g of FeCl3·6H2O were placed in separate beakers. 25mL of anhydrous ethanol was added and stirred for 30 minutes. The FeCl3·6H2O was then dripped dropwise into the CCN and stirred for another 30 minutes. 0.0073g of NH4HCO3 was then added and stirred for 10 hours. Finally, the solution was washed several times with ethanol and distilled water using a centrifuge, and the product was dried at 60°C for 24 hours.
[0034] Example 2
[0035] In the preparation of FeOOH / CCN, the amount of CCN used was 0.05 g, the amount of FeCl3·6H2O used was 0.0039 g, and the amount of NH4HCO3 used was 0.0035 g. The other steps were the same as in Example 1.
[0036] Example 3
[0037] In the preparation of FeOOH / CCN, the amount of CCN used was 0.05 g, the amount of FeCl3·6H2O used was 0.0125 g, and the amount of NH4HCO3 used was 0.0109 g. The other steps were the same as in Example 1.
[0038] Example 4
[0039] In the preparation of FeOOH / CCN, the amount of CCN used was 0.05 g, the amount of FeCl3·6H2O used was 0.0171 g, and the amount of NH4HCO3 used was 0.0149 g. The other steps were the same as in Example 1.
[0040] Example 5
[0041] In the preparation of FeOOH / CCN, the amount of CCN used was 0.05 g, the amount of FeCl3·6H2O used was 0.0378 g, and the amount of NH4HCO3 used was 0.0332 g. The other steps were the same as in Example 1.
[0042] Application of the catalyst in this application:
[0043] Photocatalytic degradation experiments of tetracycline (TC) and oxytetracycline (OTC) were conducted under visible light irradiation to determine the degradation performance of the samples. First, 5-50 mg of catalyst was added to a 20 mg / L TC or OTC solution and the reaction was allowed to proceed in the dark for 30 minutes. During this period, 4 mL of the suspension was removed every 10 minutes and centrifuged to obtain the supernatant. The photoreaction was then carried out for 120 minutes. Every 20 minutes, 4 mL of the suspension was removed and centrifuged to obtain the supernatant. Finally, the TC or OTC concentration in each supernatant was measured using a UV-visible spectrophotometer.
[0044] The formula for photocatalytic degradation rate is: D = (C0-C t ) / C0×100%.
[0045] Where: C0 is the initial concentration of TC, in mg·L 1 . C t is the concentration of TC after time t, in mg·L 1 .
[0046] For every 50 mL of 20 mg / L tetracycline or oxytetracycline solution, the amount of the catalyst can be 5 mg, 10 mg, 20 mg, 30 mg, or 50 mg.
[0047] In this study, the surface morphology of g-C3N4 was modified by hydrothermal and calcination methods to prepare coralline carbon nitride (CCN) with a unique morphology. The unique coralline morphology of CCN significantly increases the specific surface area, facilitating the transfer of photogenerated charges and providing a large number of reactive sites for the photo-Fenton system. By loading FeOOH nanodots onto CCN, a synergistic dual-reaction-center catalytic system was designed. The photocatalytic reaction center is primarily CCN, while the Fenton reaction center is primarily FeOOH, significantly enhancing the degradation rate of various pollutants.
[0048] Detailed description with accompanying drawings
[0049] Figure 1 The crystal structures of BCN, CCN, and 5%-FeOOH / CCN samples were determined by X-ray diffraction (XRD) analysis. Overall, all three samples exhibit two prominent peaks at 13.1° and 27.3°, originating from the (100) and (002) crystal planes of graphitic carbon nitride, respectively, and associated with the planar and interlayer stacking of conjugated aromatic systems. Locally, the peaks at 13.1° and 27.3° are more pronounced in BCN, while CCN and 5%-FeOOH / CCN exhibit almost no peak at 13.1°. A small peak at 27.3° appears, but it is much weaker than that of BCN. This is because CCN exhibits a unique coral-like structure compared to BCN, which significantly reduces the intensities of the two peaks. Furthermore, 5%-FeOOH / CCN, in addition to its unique structure, also has FeOOH quantum dots attached to it, further weakening the peak intensity. Figure 1 b The specific surface area and pore size distribution of BCN, CCN and 5%-FeOOH / CCN were studied by using N2 adsorption-desorption isotherms and pore size distribution curves. The specific surface areas of BCN, CCN and 5%-FeOOH / CCN were 7.03 m 2 / g, 22.15m 2 / g and 25.46m 2 / g. CCN and 5%-FeOOH / CCN possess larger surface areas than BCN, which facilitates the mass transfer of photogenerated charge carriers. Their unique coral-like structure provides more active sites for the photo-Fenton reaction. Furthermore, both CCN and 5%-FeOOH / CCN exhibit more pronounced mesoporous structures than BCN, with pore sizes around 40 nm. 5%-FeOOH / CCN exhibits significantly fewer mesopores than CCN, likely due to FeOOH occupying the mesopores, indicating a successful integration of the two.
[0050] Figure 2 Fourier transform infrared spectroscopy (FT-IR) reveals the composition of functional groups and chemical bonds of the prepared samples. The images of CCN and 5%-FeOOH / CCN are highly similar, indicating that the attachment of FeOOH has little effect on the chemical structure. 805cm -1 The nearby band is the characteristic signal of triazine unit, 1200~1700cm -1 The broad band matches the stretching vibration of the CN heterocycle, 3000-3400 cm -1 The absorption peaks between them belong to the stretching vibrations of -NH and -OH.
[0051] like Figure 3As shown in a and b, CCN presents a beautiful coral-like structure, with side branches extending from the main body. The branch diameter is about 100nm, the main body length can reach 1-2μm, and they are densely arranged. This structure can improve the utilization of light and promote the dispersion of carriers.
[0052] like Figure 4 As shown in a and b, 5%-FeOOH / CCN has dense FeOOH quantum dots attached to the special coral-like base of CCN, and its structure itself is also very three-dimensional and intricate. Figure 4 a and b are elemental mapping diagrams of 5%-FeOOH / CCN. It can be seen that FeOOH quantum dots are evenly distributed on CCN. Due to the high dispersion of the load, no lattice spacing is found between FeOOH and CCN.
[0053] like Figure 5 As shown in a, b, the samples were characterized by TEM. Figure 5 a The coral-like structure of 5%-FeOOH / CCN can be seen more clearly. Figure 5 In b, it can be clearly seen that a large number of FeOOH nanodots are attached to the CCN, and their average size is about 2 nm.
[0054] like Figure 6 As shown in a, BCN has the worst degradation performance, with a TC removal rate of only 66%. 5%-FeOOH / CCN has the best degradation performance, with a removal rate of 85%. The removal rate of CCN is 76%, which is an improvement compared to BCN. The special coral-like structure increases the active sites and allows for faster charge transfer, thereby increasing the TC removal rate. The TC removal rates of 20%-FeOOH / CCN, 10%-FeOOH / CCN, 7.5%-FeOOH / CCN and 2.5%-FeOOH / CCN are 79%, 84%, 79% and 81% respectively. The reason for this result is the loading of FeOOH nanodots on CCN. The presence of FeOOH also helps charge separation, reduces carrier recombination, and enables the photocatalytic reaction and Fenton reaction to proceed simultaneously in the reaction system, greatly improving the degradation efficiency. From this we can also know that loading more FeOOH does not necessarily lead to better performance. Excessive FeOOH self-polymerization can shield the active sites of iron, and organic ligands are easily oxidized and decomposed by reactive oxygen. Therefore, the introduction of appropriate FeOOH can achieve the best photo-Fenton performance. Figure 6b is the pseudo-first-order reaction kinetic curve and apparent rate constant k corresponding to each sample, and the k corresponding to CCN, 20%-FeOOH / CCN, 10%-FeOOH / CCN, 7.5%-FeOOH / CCN, 5%-FeOOH / CCN and 2.5%-FeOOH / CCN are 0.00877, 0.00955, 0.01099, 0.00942, 0.01242 and 0.00967 min, respectively. -1 .and Figure 6 The results in a are consistent, and the k of sample 5%-FeOOH / CCN is the largest, which also proves its highest degradation efficiency. Figure 6 Figure c shows the UV absorption spectrum of TC degradation in 5% FeOOH / CCN. TC absorbs at 360 nm. During the first 30 minutes of the dark reaction, the absorption at 357 nm remained essentially unchanged. However, during the final 120 minutes of the light reaction, the absorption gradually approached zero, indicating that TC was almost completely degraded in the photo-Fenton reaction.
[0055] Figure 7 a, b show the effect of different catalyst qualities on the TC degradation efficiency in the 5%-FeOOH / CCN system. Figure 7 As shown in a, the amount of catalyst gradually increases from 5mg to 50mg. The degradation efficiency of tetracycline first increases and then decreases with the increase of catalyst amount. The catalytic effect is the strongest when the catalyst mass is 20mg. Figure 7 When the mass of catalyst in b is 5 mg, 10 mg, 20 mg, 30 mg and 50 mg, the corresponding k are 0.00882, 0.00904, 0.01212, 0.01211 and 0.01098 min respectively. -1 , k is the largest when the mass of the catalyst is 20 mg, which further illustrates that TC will be better degraded when the mass of the catalyst is 20 mg. Figure 7 c, d show the effect of different catalyst qualities on the efficiency of OTC degradation, and there are also Figure 7 a and b have the same result. Figure 7 As shown in c, the OTC degradation rate when the catalyst mass is 20 mg is much higher than that of other masses. Figure 7 The k value at 20 mg shown in d supports this result. At this time, k = 0.01073 min -1, the largest of all degradation kinetic constants. Interestingly, for both TC and OTC, the highest pollutant degradation rate was achieved when the catalyst mass was 20 mg, placing it in the middle of the pack. This contradicts the common assumption that "more catalyst, higher degradation efficiency." This may be because an excess of catalyst hinders mass transfer efficiency, while a small amount of catalyst fails to generate sufficient electron-hole pairs and active sites, resulting in inadequate degradation efficiency.
[0056] like Figure 8 To investigate the optical properties of CCN and 5%-FeOOH / CCN, we performed UV-visible diffuse reflectance spectroscopy (UV-DRS) tests. We clearly see that 5%-FeOOH / CCN has stronger light absorption than CCN, while the absorption edge of CCN is smaller than that of 5%-FeOOH / CCN. This is due to the introduction of FeOOH nanodots.
[0057] like Figure 9 As shown, in order to explore the transfer and recombination of photogenerated electron-hole pairs on the surface of the composite material, we used steady-state photoluminescence spectroscopy (PL) for testing. It can be seen that, overall, the emission peak of the 5%-FeOOH / CCN nanocomposite is significantly weaker than that of CCN, especially at 476nm, where the difference between the two is the largest. This shows that the coupling of FeOOH and CCN can quickly separate photogenerated carriers and transfer electrons to the FeOOH surface, thereby preventing the recombination of electron-hole pairs and improving degradation efficiency. Moreover, since a large number of electrons are gathered on the FeOOH surface, they can promote the degradation of FeOOH. 3+ The reduction of Fe 2 + The problem of insufficiency.
[0058] Figure 10 This is a time-resolution transient photoluminescence test graph. Since the separation rate of electron-hole pairs is generally positively correlated with the photocurrent intensity, the higher the photocurrent intensity, the faster the electron-hole pair separation. The maximum photocurrent response of 5%-FeOOH / CCN is 0.3376μA / cm 2 , is CCN (0.1693μA / cm 2 The data show that the photocurrent intensity increases significantly after the FeOOH nanodots are coupled with CCN. This may be because after the coupling between the two, electrons are transferred from the CCN surface to the FeOOH surface, thereby suppressing the recombination of electron-hole pairs.
[0059] like Figure 11Shown are images of in situ H2O2 generation by BCN, CCN, and 5%-FeOOH / CCN. The H2O2 produced within 120 minutes was 13.43 μmol / L, 82.63 μmol / L, and 2.58 μmol / L, respectively. CCN generated over six times more H2O2 than BCN. Its unique coral-like structure significantly enhances CN's H2O2 production capacity. The 5%-FeOOH / CCN self-Fenton system consumes significant amounts of H2O2, resulting in minimal H2O2 production. The H2O2 required for the Fenton reaction, with FeOOH as the reaction center, can be spontaneously generated by this CCN.
[0060] The above is a schematic description of the present invention and its embodiments, which is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by the above and does not deviate from the technical solution of the present invention, and according to the technical essence of the present invention, he or she can design a structure and implementation similar to the above embodiment without inventiveness, such design shall fall within the scope of protection of the present invention.
Claims
1. A dual-functional iron oxyhydroxide nanodot / coral-like carbon nitride catalyst, characterized by: The catalyst presents a coral-like structure, with side branches extending from the main body. The branch diameter is about 100 nm, the main body length can reach 1-2 μm, and the branches are densely arranged.
2. A method for preparing an iron oxyhydroxide nanodot / coral-like carbon nitride bifunctional catalyst, characterized by: CCN was synthesized by hydrothermal and calcination methods, and then the FeOOH quantum dots / CCN composite catalyst was prepared by template-free and additive-free in-situ co-precipitation technology.
3. The method for preparing the iron oxyhydroxide nanodot / coral-like carbon nitride bifunctional catalyst according to claim 2, characterized in that: Preparation of CCN: First, urea was added to a beaker of deionized water and stirred for 30 minutes. Then, melamine was added and stirred for 180 minutes to prepare a precursor solution. The solution was then transferred to a reactor and placed in an oven at 180°C for 20 hours to a filling degree of 80%. After the container was naturally cooled, the solution was repeatedly washed with ethanol and water using a centrifuge. Finally, the product was dried at 60°C for 24 hours. Preparation of FeOOH / CCN: First, CCN and FeCl3·6H2O were placed in beakers respectively, anhydrous ethanol was added, and the mixture was stirred for 30 min. FeCl3·6H2O was added dropwise into CCN and stirred again for 30 min. Then NH4HCO3 was added and stirred for 10 h. Finally, the solution was washed several times with ethanol and distilled water through a centrifuge, and the product was dried at 60°C for 24 h.
4. The method for preparing the iron oxyhydroxide nanodot / coral-like carbon nitride bifunctional catalyst according to claim 2, characterized in that: In the preparation step of FeOOH / CCN, the molar ratio of FeCl3··6H2O to NH4HCO3 is 1:3, and the weight ratio of CCN to FeCl3·6H2O is 1.32-12.82:
1.
5. The method for preparing the iron oxyhydroxide nanodot / coral-like carbon nitride bifunctional catalyst according to claim 2, characterized in that: In the preparation step of CCN, the usage ratio of urea to melamine is 1.6:
1.
6. Use of the photocatalyst prepared according to the preparation method according to any one of claims 2 to 5 in photocatalytic degradation of tetracycline and oxytetracycline.
7. The use according to claim 6, characterized in that: Photocatalytic degradation experiments of TC and OTC were carried out under visible light irradiation to determine the degradation performance of the samples. First, 5-50 mg of catalyst was added to a 20 mg / L TC or OTC solution and reacted in the dark for 30 minutes. During this period, 4 mL of the suspension was taken out every 10 minutes and centrifuged to obtain the supernatant. Then, a photoreaction was carried out for 120 minutes. 4 mL of the suspension was taken out every 20 minutes and centrifuged to obtain the supernatant of the photoreaction process. Finally, the concentration of TC or OTC in each supernatant was determined using a UV-visible spectrophotometer. The formula for photocatalytic degradation rate is: D = (C0-C t ) / C0×100%, Where: C0 is the initial concentration of TC, in mg·L 1 . C t is the concentration of TC after time t, in mg·L 1 .
8. The use according to claim 7, characterized in that: In every 50 mL of tetracycline solution, the amount of the catalyst is 5 mg, 10 mg, 20 mg, 30 mg or 50 mg.